Optimization of Three-Roll Mill Parameters for In-Situ Exfoliation of Graphene. Issue 19 (14th March 2016) - Li, Yan; Zhang, Han; Bilotti, Emiliano; Peijs, Ton
ABSTRACT: Three-roll milling (TRM) has proven to be an effective method to disperse 1D nanofillers like carbon nanotubes in polymer resins. However, until now only limited research has been performed on using this method to exfoliate and disperse 2D nanofillers, such as graphene and graphene nanoplatelets (GNP) with preserved lateral dimension. In the present work, a systematic study of TRM processing parameters on final nanocomposite properties is presented, resulting in improved GNP/epoxy nanocomposite properties after the optimization of TRM parameters such as mode, speed, cycles, gap distance, and resin temperature. Electrical conductivity of the final GNP/epoxy nanocomposites is increased by six orders of magnitude, while at the same time a high mechanical reinforcement is achieved as well.